A Feasibility Study on MedPro Phils RMS 2000 - Barro, Jesselyn B.; Bularan, Melanie; Chu, Ma. Rosario B.; Tiu, Venice (Diliman, Quezon City College of Engineering, 2000)
MedPro RMS is a telemedicine system with a specially designed software and electronic interface which enables control of a microscope from a computer, for use in pathology and other fields of medicine. The program offers remote manipulation of the microscope?s settings with the use of the software and interface board. The software enables off-site control of the microscope by sending signals over a telecommunications network, such as the Internet or an organization?s local area network (LAN). RMS 2000 will be the first locally manufactured telemedicine system in the country. Through market segmentation and target marketing, it was identified that the products? market consists of secondary and tertiary hospitals. Historical demand and supply were determined through a field test and competitor analysis. Demand and supply analysis revealed that there is zero gap, meaning foreign competitors have the capability of supplying the demand. The company is confident that it can compete with foreign brands relying on its competitive advantage of lower cost, superior quality and excellent after-sales service. Market share was determined using percent willingness. Market share is 34% for secondary hospitals and 73% for tertiary hospitals. The sales plan for 2001-2005 was determined to be: 82 units for 2001, 114 units for 2002, 190 units for 2003, 191 units for 2004 and 165 units for 2005. For the marketing strategy, product, pricing, placement and promotions strategies were determined. The chosen product name was RMS 2000 and it will be priced at P270,000 per unit. The product will be sold through distributors who will be given a 16% commission. For promotions, the company will hold a product launching and product demos, distribute brochures and product video on CDs and place ads in a medical journal and maintain in its own website. The production plan resulted to a production level of 86, 116, 194, 191, and 163 for years 1-5. There will be 8 hours / day and 5 days / week in the production of RMS 2000 with a capacity of 267 units/ year. Safety stock level is set at 5% of sales plan. It was determined from the capacity plan and aggregate plan that 1 engineer and 1 technician are enough to satisfy the demand for RMS 2000. For the material requirements plan, annual PCB requirements are ordered a month before year of concern while the monthly requirements of all other components are ordered a week before the month they are needed. The plant will be located at Dasmariñas corner T. Pinpin St. Binondo Manila, with a lot size of 113 m2. This has been decided after thorough evaluation. The total project cost to start the business venture is Php 3,875,657.25. A one month pre-operation period and a three-month working capital are used. Half of the project cost will be financed through stockholder?s equity while the other half will be loaned from Metrobank. The loan will be paid in five years with an annual interest of 14%. Financial statements like the income statement, cash flow projections and balance sheet for the operating period and the five-year study period were generated. The cash flow projections indicate a positive net cash flow of 3,849,090.18 for the first year and a continuing positive trend in the remaining four years of the five-year study period. It can be seen from the income statement that the income of the project is increasing for the next five years. The balance sheet shows that the assets and retained earnings of the company are increasing for the next five years. This is due to the increase in sales. From the financial analysis, the financial ratios show a stable financial and profitable position for the company in the next five years. The ratios show that the company becomes more stable and profitable through the years. The test for liquidity that shows an increasing trend therefore the company is becoming more liquid for the duration of the study period. The test for debt coverage shows a trend of increasing funds that means that the company ability to pay its debt increases. The sensitivity analysis shows that the payback period is 4.68 months; therefore, the project is worth undertaking as there is only a short payback period. Also the breakeven volume, selling price and sales are well under the projected selling volume and projected selling price. The company returned an NPV of a positive value of 13,969,357.14 and IRR of 295.55% which is significantly higher than the MARR of 30%. Both of these indicate that the project is an acceptable business venture. Based on evaluation of several factors, it was determined that the form of ownership most suitable for the production of RMS 2000 is a corporation. The company will hire the following for its management staff and other personnel; general manager, production manager, sales and marketing manager, accountant, engineer, technician, secretary/bookkeeper, driver, janitor and security guard. They will be given basic salary plus other benefits such as SSS, Medicare and 13th Month pay. In the social profitability analysis of the project, the benefits that were generated are the income-generating jobs it provides, the amount of taxes to be paid to the government, the utilization of local business and utilities, the promulgation of research and development, and modernization of local hospitals. The usage of non-biodegradable raw materials is the only disbenefit that was found. From the analysis of the quantitative benefits/disbenefits and qualitative benefits/disbenefits, it can be concluded that the project is socially profitable. In all aspects of the study, the project was proven to be FEASIBLE.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: MedPro Philippines Inc; Medical microscopy; Participatory monitoring and evaluation (Project management)